Province of Santa Fe, Republic of Argentina : Public Financial Management Assessment - World Bank (CC BY 3.0 Unported, 2012)
The assessment for the Province of Santa Fe was prepared jointly by the Ministry of Finance of the Province of Santa Fe and the World Bank (WB) on the basis of findings from missions. It seeks to: (i) provide the provincial government with a reference tool for dialogue and action to strengthen their public financial management systems; (ii) assess the province's PFM systems and identify and address their main fiduciary issues, as well as their impact on the implementation of World Bank operations; and (iii) contribute in a broader sense to the dialogue between the Bank and Argentina's national and provincial authorities regarding fiduciary portfolio management and reliance on the country's systems. The assessment is not a fully fledged PFM performance report using all PEFA performance indicators. As agreed with the provincial government and the World Bank s Country Management Unit, the team selected and used 19 PFM performance indicators (PI 1, PI 4, PI 5-7, PI 9-12, PI 16-18, and PI 20-26) to review the status of PFM in the province. The report was prepared based on the findings of the missions that visited Argentina in the first semester of 2009 and refers to the 2006-2008 fiscal years. The report was completed in June 2012 and highlights the progress and improvement in some PFM areas since 2009 whenever provided by the Province (in footnotes wherever appropriate).